A low-cost interface for multi-electrode array data acquisition systems. (October 2008) - Serra, Michael; Chan, Amy; Dubey, Maya; Shea, Thomas B.
Multi-electrode array systems have enabled the in vitro electrophysiological study of neuronal networks. The data processing component of these systems consists of an advanced computer system and data acquisition electronics that collectively cost more than the multi-electrode arrays and amplifiers. Considering that these elaborate systems may be cost-prohibitive for many laboratories, we have developed a simple but novel method for recording groups of related multi-electrode array channels with a low-cost data acquisition system.